Governance with multiple objectives: Evidence from top executive turnover in China - Chang, Eric C.; Wong, Sonia M.L. (Journal of Corporate Finance, 2009)
We examine the relationship between Chief Executive Officer (CEO) turnover and the performance of listed Chinese firms and obtain two results. First, we find a negative relationship between the level of pre-turnover profitability and CEO turnover when firms are incurring financial losses, but no such relationship when they are making profits. Second, there is an improvement in post-turnover profitability in loss-making firms, but no such improvement in profit-making firms. These results indicate the existence of a time-varying objective function, whereby shareholders have a greater incentive to discipline their CEOs on the basis of financial performance when their firms are incurring financial losses rather than profits.